Analisis dan Pengujian Sistem Informasi Penjualan Produk UMKM Menggunakan Metode Scrum - Gladiola Lavinia Ambayu; Kristoko Dwi Hartomo (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
In Indonesia, developments in the large-scale to small-scale business sectors are beginning to emerge. One of them is MSMEs that utilize patchwork waste. Sometimes in running their business, business owners have difficulty finding patchwork. Based on the issues, e-commerce is an alternative solution to accommodate the sale of patchwork. The benefits of e-commerce for MSMEs are provide flexibility in production, send and receive offers quickly and efficiently, and conduct marketing with the aim of global markets. The method used in this study is the scrum method. Scrum was chosen because of its flexibility, so that it can produce quality software that suits the user, can be used in large and small projects, and easy to adopt changes. The scrum method consists of 5 stages, starting with the product backlog, sprint planning, daily scrum, sprint review, and sprint retrospective. The results of this study are to provide convenience in system design, such as anticipating changes in requirements during the system development process. The purpose of this study is to make it easier for users to find patchwork and help patchwork sellers in expanding the market.